INTEGRASI PASAR KEUANGAN INDONESIA DI ASEAN: PENDEKATAN FORWARD LOOKING - WIHANA KIRANA JAVA; HERMADA DEKIAWAN (Journal of Indonesian Economy and Business (JIEB), 1997)
This paper tries to analize the Indonesian financial integrated market inAsean, except Brunei and Vietnam. In this paper, integration expressed by the respond of interest rate to the forward discount/premium curs in the cross rate. In general economic actors judge his actual decision based on backward looking, but in this research, will analized the impact of society expectation for the future period to the actual decision. The forward looking method in this paper is using the co-integration approach and long term unit of F.CM (Error Correction Model) from the data performance. The outcome shows that the community performance in financial integrated market as showed by the interest rate respond to the forward curs, significantly. However, the impact is still relatively small. Forward looking significance indicates tiiat the actual condition is influenced by community expectation about the future.